2019
DOI: 10.1042/bcj20190687
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric changes in HDM2 by the ATM phosphomimetic S395D mutation: implications on HDM2 function

Abstract: Allosteric changes imposed by post-translational modifications regulate and differentiate the functions of proteins with intrinsic disorder regions. HDM2 is a hub protein with a large interactome and with different cellular functions. It is best known for its regulation of the p53 tumour suppressor. Under normal cellular conditions, HDM2 ubiquitinates and degrades p53 by the 26S proteasome but after DNA damage, HDM2 switches from a negative to a positive regulator of p53 by binding to p53 mRNA to promote trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…It has been shown that under DNA damage conditions, the kinase ATM is activated and phosphorylates MDM2 in Ser 395 (Maya et al , 2001). This post‐translational modification stimulates a change in MDM2 conformation that promotes a switch in its activity (Medina‐Medina et al , 2016; Uhrik et al , 2019); initially, a ubiquitin ligase for the tumour suppressor p53, it becomes a translation factor for p53 (Candeias et al , 2008; Medina‐Medina et al , 2016). We have previously shown that mutant MDM2(S395D) mimic the Ser 395 phosphorylation promoted by ATM under DNA damage conditions (Gajjar et al , 2012; Medina‐Medina et al , 2016; Uhrik et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that under DNA damage conditions, the kinase ATM is activated and phosphorylates MDM2 in Ser 395 (Maya et al , 2001). This post‐translational modification stimulates a change in MDM2 conformation that promotes a switch in its activity (Medina‐Medina et al , 2016; Uhrik et al , 2019); initially, a ubiquitin ligase for the tumour suppressor p53, it becomes a translation factor for p53 (Candeias et al , 2008; Medina‐Medina et al , 2016). We have previously shown that mutant MDM2(S395D) mimic the Ser 395 phosphorylation promoted by ATM under DNA damage conditions (Gajjar et al , 2012; Medina‐Medina et al , 2016; Uhrik et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this mutant is also able to bind and ubiquitinate the RB protein. It has been reported that this phosphorylation changes the conformation and switches the activity of MDM2 from a ubiquitin ligase acting on p53 to a translation factor acting through a direct interaction between MDM2 and the p53 mRNA (Medina‐Medina et al , 2016; Uhrik et al , 2019). Although the parallelism is evident, the mechanism is not the same.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, activated ATM phosphorylates MDM2 on Ser395, which switches MDM2 from a negative to a positive regulator of TP53 mRNA translation. However, in the absence of the TP53 mRNA-MDM2 interaction, Ser395 phospho-MDM2 has a greater capacity to ubiquitinate p53, leading to its degradation [145][146][147]. In addition, the interplay between MDM2-ATM-p53 and TP53 mRNA plays a significant role in p53 stabilisation [148].…”
Section: Pi3k/akt Pten Mtor and Autophagymentioning
confidence: 99%
“…For the former, the N-terminal domain of MDM2 represents an important interaction interface for many proteins such as p73, p63, DP1, HAUSP, hTERT, NUMB and NOTCH [ 193 ], and MDM2 inhibitors that bind to this domain potentially abolish these interactions. Moreover, MDM2 exhibits structural plasticity and allosteric changes impact its functions [ 145 , 194 ], implying that not only N-terminal interacting proteins are influenced by MDM2 inhibitors. One of the first pieces of evidence for a p53-independent action of nutlin-3 came from Ambrosini et al in 2007.…”
Section: Sensitivity To Mdm2 Inhibitorsmentioning
confidence: 99%